2007
DOI: 10.1111/j.1654-1103.2007.tb02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance and environmental factors as drivers of long‐term post‐fire regeneration patterns in Mediterranean forests

Abstract: Question: What are the main forces driving natural regeneration in burned mature Mediterranean forests in the medium‐long term and what are the likely successional trajectories of unmanaged vegetation? Location: Valencia Region, eastern Spain. Methods: A wildfire burned 33 000 ha of Pinus halepensis and P. pinaster forest in 1979, and subsequent smaller wildfires took place between 1984 and 1996. The study was designed to sample the range of environmental and disturbance (fire recurrence and land use) condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 38 publications
8
101
0
2
Order By: Relevance
“…Our results agree with the conceptual model proposed by Baeza et al (2007), which suggested that stable communities composed of C. albidus and U. parviflorus would become established in old-fields of SE Spain when the fire intervals were less than 10 years. Hence, our work evidences that old-field successions could behave like other Mediterranean ecosystems; where fire recurrence is high the dominance of small-size shrubs and herbs is promoted (Zedler et al 1983;Haidinger and Keeley 1993;Baeza et al 2007).…”
Section: Succession In Mediterranean Old-fieldssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with the conceptual model proposed by Baeza et al (2007), which suggested that stable communities composed of C. albidus and U. parviflorus would become established in old-fields of SE Spain when the fire intervals were less than 10 years. Hence, our work evidences that old-field successions could behave like other Mediterranean ecosystems; where fire recurrence is high the dominance of small-size shrubs and herbs is promoted (Zedler et al 1983;Haidinger and Keeley 1993;Baeza et al 2007).…”
Section: Succession In Mediterranean Old-fieldssupporting
confidence: 93%
“…In fire-prone ecosystems, deviations from the expected successional pathways have been proposed especially where there is a high fire recurrence over relatively short time periods (Noble and Slatyer 1980;Trabaud 1991;Eugenio and Lloret 2004;Donato et al 2009). As a consequence vegetation can be diverted to communities composed mainly of small-sized species with high proportion of fine fuels, which can provide a positive feedback on the likelihood of fire recurrence (Zedler et al 1983;Haidinger and Keeley 1993;Baeza et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Desertification in the north is driven by intensive irrigation and by past and current over-exploitation of the vegetation, e.g., by livestock pressure, all driven by markets and regional agricultural policies, whereas desertification in Africa is driven more by the increased encroachment of rangeland by cultivation or livestock production in recent decades due to the exponential growth in population [193]. Moreover, community succession and soil processes after fires and/or increasing droughts in Mediterranean plant communities have created patchy vegetation and accelerated soil degradation [194], reducing water infiltration [195], all of which lead to desertification. Several Mediterranean areas of European countries have been subjected to land-use change in recent decades [196][197][198], whereby unproductive areas were forested, abandoned or overexploited [198].…”
Section: Shifts In Forest Cover and Carbon Uptakementioning
confidence: 99%
“…This phenomenon was already described in literature, e.g. by Cerdà [1998c], Rey Benayas et al [2007] and Baeza et al [2007].…”
Section: Catchment Characteristicsmentioning
confidence: 76%
“…This dynamic is typical of many Mediterranean catchments, which suffered strong land abandonment during the 1960s, inducing accelerated land degradation and the development of a shrub cover, as is the case of the Rambla del Poyo catchment. This behaviour was mentioned in various studies, such as Cerdà [1998], Rey Benayas et al [2007] and Baeza et al [2007].…”
Section: Temporal Validation Of the Sedimentological Submodelmentioning
confidence: 99%